2017
DOI: 10.4103/ijmy.ijmy_168_17
|View full text |Cite
|
Sign up to set email alerts
|

Association between effectiveness of tuberculosis treatment and cytochrome P-4502E1 polymorphism of the patients

Abstract: Polymorphism of CYP2E1 genotype is an important criterion for the development of hepatotoxicity before and during TB treatment while increased rifampicin level has no influence on it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This could be explained by a higher serum concentration of rifampicin and slightly higher serum concentration of isoniazid in patients with *AA genotype, compared to the group of *AG genotype carriers. At the same time, according to previous studies, according to the CYP3A4*1G genotype, in "slow metabolizers" (mutant homozygous genotype), the risk of developing of hepatotoxicity during anti-tuberculosis therapy exceeded the similar indicator of "rapid metabolizers" [9].…”
Section: клінічна практикаmentioning
confidence: 72%
See 1 more Smart Citation
“…This could be explained by a higher serum concentration of rifampicin and slightly higher serum concentration of isoniazid in patients with *AA genotype, compared to the group of *AG genotype carriers. At the same time, according to previous studies, according to the CYP3A4*1G genotype, in "slow metabolizers" (mutant homozygous genotype), the risk of developing of hepatotoxicity during anti-tuberculosis therapy exceeded the similar indicator of "rapid metabolizers" [9].…”
Section: клінічна практикаmentioning
confidence: 72%
“…For example, TB patients with "slow metabolizers" (SM) genotype of CYP2C9 gene had the highest serum isoniazid and rifampicin level and the most favorable treatment outcome comparatively to "rapid metabolizers" (RM) genotype group [8]. According to CYP3A4*1B genotype in TB patients with RM genotype, the indexes of cytolysis (alanine aminotransferase, aspartate aminotransferase and bile stasis (gamma-glutathione transferase) were higher comparatively to SM genotype both before and after in-patient treatment [9]. According to the literature, the enzyme cytochrome (CYP) 3A4/5 is involved in the metabolism of more than a one-third of all drugs [10].…”
Section: клінічна практикаmentioning
confidence: 99%
“…CYP2E1 also increased in mPxr −/− mice treated with both rifampicin and isoniazid (1.47-relative change). Polymorphisms associated with increased CYP2E1 activity in humans increase the incidence of drug-induced liver injury (DILI) [ 42 , 43 , 44 ]. Inhibiting CYP2E1 is protective against isoniazid-induced hepatotoxicity in mice [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous chemotherapy increases the concentration of ATD in the blood in a short period of time, ensures a rapid access of these drugs to the focus of tuberculous inflammation and the use of solutions of intravenous ATD provides faster detoxication in patients with TB [15,22]. In addition, the results of studies during the past years have proved that the antimicrobial effect of ATD depends only on their maximum concentration in the blood, whereas the duration of contact with MBT is not significant [10,25]. We demonstrated that intravenous administration of ATD allows creating a high level of bacteriostatic blood activity and maximum concentration in blood serum of patients as much as 2.5 times higher compared to oral use.…”
Section: Discussionmentioning
confidence: 99%